Observation of a transition state resonance in the integral cross section of the F+HD reaction - Skodje, RT; Skouteris, D; Manolopoulos, D; Lee, S; Dong, F; Liu, K (2000)
We have studied the reaction F+HD at low collision energies using a combination of experimental and theoretical methods. Clear evidence for a reactive resonance is found in the integral cross section for the reactive channel F+HD→HF+D. Using a crossed molecular beam apparatus, the total reactive cross sections for the HF+D and DF+H channels were obtained in the collision energy range of 0.2-5 kcal/mol. In addition, Doppler profiles were obtained over this range of energies, which provide information about the angularly resolved distribution of final vibrational states. The cross section shows a distinctive steplike feature near 0.5 kcal/mol. Furthermore, the Doppler profiles reveal a dramatic change in the angular distribution of products over a narrow energy range centered at 0.5 kcal/mol. This feature is shown to arise from a reactive resonance localized near the transition state. Theoretical scattering calculations have been carried out using the Stark-Werner potential energy surface, which accurately reproduce the shape of the resonance feature. A detailed analysis of quantum dynamics using the spectral quantization method reveals that a quantum resonance exists near 0.52 kcal/mol, which is localized about the collinear FHD geometry. At collision energies below 1 kcal/mol, the reaction was found to proceed almost exclusively through resonant tunneling with very little contribution from direct, over the barrier, reaction. The properties of the quantum resonance, such as the position, lifetime, and partial widths were found to correlate well with the experimental results and the quantum scattering calculations. © 2000 American Institute of Physics.